Bovine Gamma Delta T Cells Contribute to Exacerbated IL-17 Production in Response to Co-Infection with Bovine RSV and Mannheimia haemolytica - McGill, Jodi L.; Rusk, Rachel A.; Guerra-Maupome, Mariana; Briggs, R. E.; Sacco, R. E. (My University, 2016)
Human respiratory syncytial virus (HRSV) is a leading cause of severe lower respiratory tract infection in children under five years of age. IL-17 and Th17 responses are increased in children infected with HRSV and have been implicated in both protective and pathogenic roles during infection. Bovine RSV (BRSV) is genetically closely related to HRSV and is a leading cause of severe respiratory infections in young cattle. While BRSV infection in the calf parallels many aspects of human infection with HRSV, IL-17 and Th17 responses have not been studied in the bovine. Here we demonstrate that calves infected with BRSV express significant levels of IL-17, IL-21 and IL-22; and both CD4 T cells and Upsilon delta T cells contribute to this response. In addition to causing significant morbidity from uncomplicated infections, BRSV infection also contributes to the development of bovine respiratory disease complex (BRDC), a leading cause of morbidity in both beef and dairy cattle. BRDC is caused by a primary viral infection, followed by secondary bacterial pneumonia by pathogens such as Mannheimia haemolytica. Here, we demonstrate that in vivo infection with M. haemolytica results in increased expression of IL-17, IL-21 and IL-22. We have also developed an in vitro model of BRDC and show that co-infection of PBMC with BRSV followed by M. haemolytica leads to significantly exacerbated IL-17 production, which is primarily mediated by IL-17-producing Upsilon delta T cells. Together, our results demonstrate that calves, like humans, mount a robust IL-17 response during RSV infection; and suggest a previously unrecognized role for IL-17 and Upsilon delta T cells in the pathogenesis of BRDC.
Citation: McGill, J. L., Rusk, R. A., Guerra-Maupome, M., Briggs, R. E., & Sacco, R. E. (2016). Bovine Gamma Delta T Cells Contribute to Exacerbated IL-17 Production in Response to Co-Infection with Bovine RSV and Mannheimia haemolytica. Plos One, 11(3), 20. doi:10.1371/journal.pone.0151083
Keywords: Respiratory Syncytial Virus; Viral-Infection; Mycobacterium-Bovis; Cytokine Production; Animal-Models; Wild-Type